Effects of acute supplementation of Panax ginseng on endurance running in a hot & humid environment - Wong, Fadzel Chee Ping; Chen, Chee Keong; Amit Bandyopadhyay (New Delhi : Council Of Medical Research, 2011)
BACKGROUND & OBJECTIVES: Athletes in Malaysia need to perform in a hot and humid environment due to the climatic nature of the country. Chronic supplementation of Panax ginseng (PG) (a deciduous perennial plant belonging to the Araliaceae family) enhances physical performance. As the ergogenic effect of acute supplementation of PG on endurance performance has not been explored in the Malaysian population especially in a hot and humid condition this study was taken up.